Pengaruh Amenitas Terhadap Tingkat Kepuasan Pengunjung di Museum 10 November Surabaya - Nusantara, Mhd Dharma Samudra; Wahyuni, Wahyuni (Lembaga Teewan Journal Solutions, 2026)
The 10 November Museum Surabaya is one of the historical tourism destinations with significant educational value. However, several amenity-related issues remain, including inadequate toilet cleanliness, limited sanitation facilities, insufficient exhibition room comfort, and less accessible supporting facilities. These conditions may reduce visitor satisfaction. This study aims to analyze the effect of amenity quality on visitor satisfaction at the 10 November Museum Surabaya and provide recommendations for facility improvement. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 100 visitors selected using an accidental sampling technique. The data were analyzed using validity tests, reliability tests, normality tests, simple linear regression analysis, t-tests, and the coefficient of determination (R²). The results indicate that amenity quality has a positive and significant effect on visitor satisfaction. The t-test produced a calculated t-value of 4.359 with a significance level of 0.000 (<0.05), indicating that the research hypothesis is accepted. The simple linear regression analysis resulted in a regression coefficient of 0.321, showing a positive relationship between amenity quality and visitor satisfaction. The coefficient of determination (R²) was 0.162, indicating that amenity quality contributes 16.2% to visitor satisfaction. In conclusion, improving amenity quality, particularly toilet cleanliness, sanitation facilities, exhibition room comfort, and other supporting facilities, can enhance visitor satisfaction. This study contributes to museum management by providing a basis for evaluating and improving facilities to enhance service quality and visitor experiences.